Newsletter: UiTM Faculty of Music: UiTM Music Series 2016 / Faculty of Music, UiTM Shah Alam (Faculty of Music, UiTM Shah Alam, 2016)
Sekretariat Mahasiswa Fakulti(SMF) and University Chamber Choir (UCC) are going to visit Sabah from 29th Jan - 2nd Feb, 2016 supported under Ministry of Culture Sabah and UiTM Faculty of music . Our destination will be in KK and Tambunan. The purpose of this E- community project is to share our high quality musical performance for Sabah local people including secondary school students. UCC will be having a full choral concert at Sabah Cultural Center on 30th January, UCC and SMF will visit SMK Tambunan for 2 days where we will provide mini concert, workshop. We also utilize online system for provide musical lessons and support local educators. We believe it will be wonderful opportunity for all of us and hope many of students in Sabah will be interested in studying at UiTM in future.